UML-based Requirements Analysis on Risk Pre-control System in Coal Enterprise - Huang Hui; Yin Dongyue (Institute of Advanced Engineering and Science, 2013)
Combining with the present situation of risk management in domestic coal enterprises,the overall flow of risk pre-control system of coal enterprise is designed on the basis of the ISO/FDIS31000 “Risk management—Principles and guidelines” released by the International Standards Organization and risk precontrol management system of safety in coal mine, UML(unified modeling language) is used as a tool to establish the model of system requirements analysis, risk management subsystem is taken as an example to elaborate the modeling process of system analysis, the merit of ensuring the accuracy and consistency of system analysis when using UML as the tool of object-oriented system requirements analysis is verified. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2853